8 Diagnostic performance of ECG detection of left atrial enlargement in patients with arterial hypertension relative to the cardiac magnetic resonance gold-standard: Impact of obesity. (18th April 2016) - Erdei, T; Rodrigues, JC; McIntyre, B; Dastidar, A Ghosh; Burchell, AE; Ratcliffe, L; Hart, EC; Paton, JF; Hamilton, M; Nightingale, AK; Manghat, NE
Abstract : ECG may demonstrate evidence of left atrial enlargement (LAE), which has adverse prognostic implications. We sought to determine the accuracy of 5 ECG criteria of LAE in a hypertensive cohort relative to CMR and to investigate the confounding effect of obesity. Methods: Consecutive referrals for CMR from a tertiary hypertension clinic were reviewed. Patients with any concomitant cardiac pathology were excluded. ECGs were assessed, blinded to CMR data, for: 1) P wave >110ms, 2) P-mitrale (notched P wave with inter-peak duration >40ms), 3) P wave axis <30°, 4) Area of negative P terminal force in lead V1 (NPTF-V1) >40msmm and 5) Positive P terminal force in aVL (PPTF-aVL) >0.5mm. Maximal LA volume index (LAVI) was measured by the biplane area-length method. Results: 130 patients were included (age: 51.4 ± 15.1 years, 47% male, 51% obese, systolic blood pressure: 171 ± 29 mmHg, diastolic blood pressure: 97 ± 15 mmHg). The prevalence of LAE by CMR was 26% and by ECG varied from 1% (P-mitrale) to 27% (P axis <30 o ), and was 46% when ≥1 ECG LAE criteria were present. There was no significant difference in mean LAVI when ≥1 ECG LAE criterion was present compared to when no ECG LAE criteria were present (47 ± 15 vs 50 ± 15 ml/m 2, p = 0.235). All the individual ECG LAE criteria were more specific than sensitive (Table 1/A ), with specificities ranging from 70% (P axis <30 o ) to 99% (P-mitrale). Obesity attenuated the specificity of most of the individual ECG LAE criteria (Table 1/B ). Obesity correlated with significant lower specificity (48% vs 65%, p < 0.05) and a trend towards lower sensitivity (59% vs 43%, p = 0.119) when ≥1 ECG criteria of LAE were present. Conclusion: Individual ECG criteria of LAE in hypertension are specific, but not sensitive, for identifying anatomical LAE, relative to CMR. LAE in hypertension should not be excluded on the basis of the ECG, particularly in obese subjects.